MALHERBE, D.F. DU T. Inventory of documents - MALHERBE, D.F. DU T. (ARCA, 2018)
Minutes; correspondence; speeches; articles, pamphlets, photos regarding the National Party and mining
COVERAGE: 1910-1961; 1.00 metres
Keywords: MALHERBE, D.F. DU T.; Inventories; Politicians; National Party